A population‐based, retrospective cohort study of the association between ABO blood group and risk of COVID‐19. (26th November 2022) - Dahlén, Torsten; Li, Huiqi; Nyberg, Fredrik; Edgren, Gustaf
Abstract: Background: Several studies have investigated associations between ABO blood group and risk of COVID‐19, with inconsistent results. Objective: To study associations between ABO blood group and risk of different stages of COVID‐19. Methods: The study was based on nationwide registers encompassing all blood‐grouped persons in Sweden, and all of their COVID‐19‐related outcomes. Associations between ABO blood group and COVID‐19 outcomes were estimated using Poisson regression models. Analyses were conducted overall and stratified by vaccination status. Results: A total of 4, 986, 878 individuals were included. The incidence rate ratios of testing positive for COVID‐19 were 1.08 (95% confidence interval [CI], 1.07–1.08), 1.06 (95% CI, 1.05–1.07), and 1.01 (95% CI, 1.00–1.01) for blood groups A, AB, and B, respectively, as compared to O. Similar associations were seen for risk of hospital admissions, intensive care unit admissions, and risk of death. For most outcomes, associations with ABO blood group were much attenuated or even reversed in vaccinated individuals. Conclusions: Individuals with blood groups A, AB, and B are at increased risk of contracting COVID‐19 as well as developing more severe forms of the disease.